Fish distributions in a tidal channel indicate the behavioural impact of a marine renewable energy installation - Shaun Fraser; Benjamin J. Williamson; Vladimir Nikora; Beth E. Scott (Energy Reports, 2018)
In the dynamic environments targeted for marine renewable energy extraction, such as tidal channels, the natural distribution of fish and behavioural impacts of marine renewable energy installations (MREIs) are poorly understood. This study builds on recent methodological developments to reveal the behaviour of fish schools using data collected by a seabed-mounted echosounder deployed in extreme tidal flows and in the wake of a MREI (composed of the foundation of a full-scale tidal stream energy turbine). The results show a significant change (p<0.001) in the vertical distribution of fish schools in the vicinity of a MREI compared to a nearby control location representative of the natural conditions. The MREI is associated with an overall increased rate of fish school observations (+74%), particularly at night (+163%) and in the MREI wake flow (+378%), related to the disruption of natural diurnal behavioural patterns in school characteristics (size, relative density, and distance from seabed). These results indicate an attraction effect of the MREI, and show that the aggregation and vertical distribution of fish in the modified flow conditions is dependent on tidal phase with evidence of avoidance of the MREI depth range during peak flow velocities. The behavioural responses observed in this study provide new information relevant to the environmental impact assessment of marine renewable energy developments and highlight priorities for further research.
Keywords: 330; Environmental impact; Fish behaviour; Tidal flow; Tidal stream energy